The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/8971654
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV/AIDS Infection among Sexually Active Women in Ethiopia: Further Analysis of 2016 EDHS

Abstract: Background. The issue of HIV/AIDS is prevalent around the world and in Ethiopia as well. The aim of this study was to determine the prevalence and risk factors of HIV/AIDS infection among sexually active women in Ethiopia. Methods. For this study, data were obtained from the Ethiopia Demographic and Health Survey conducted in 2016. This study contains 11,729 women who have had at least one episode of sexual intercourse in their lifetime. Interviewers for voluntary HIV testing collected finger-prick blood speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Having multiple sexual partners in life increases the odds of HIV infection. This is consistent with findings from other studies ( 17 , 18 ). Sexually active women residing in urban areas had higher odds of HIV infection compared to sexually active women living in rural areas.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Having multiple sexual partners in life increases the odds of HIV infection. This is consistent with findings from other studies ( 17 , 18 ). Sexually active women residing in urban areas had higher odds of HIV infection compared to sexually active women living in rural areas.…”
Section: Discussionsupporting
confidence: 94%
“…Those with primary and secondary education had higher odds of HIV infection as compared to women who had no education. Previous studies have found that better levels of education are related to an increased risk of HIV infection due to the fact that more educated women are more likely to be mobile and have more sexual partner networks ( 17 ). Being widowed, divorced, or separated was found to be significantly associated with higher odds of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher rates of HIV/AIDS in urban areas due to factors such as increased mobility, higher population density, and greater access to healthcare services, and the global HIV/ AIDS epidemiology reported that young adults are often at higher risk of HIV infection due to behavioral factors, including engaging in risky sexual behaviors and substance abuse. Low educational attainment is often associated with limited health literacy, which can hinder individuals' ability to understand and adopt preventive measures against parasitic infections (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The study ndings are consistent with studies in Sierra Leone [20] and China [33] which reported that women in urban areas had a greater association with HIV infection risk factors. This may be because women in urban areas are exposed to a high population density with risky populations like long-distance truck drivers inclusive hence a high likelihood of indulging in risky sexual behaviour [34,41]. Moreover, region was also found to be associated with risk factors for HIV, where the western region compared to Kigali had lower odds of facing HIV risk factors.…”
Section: Discussionmentioning
confidence: 99%